Black-box Concurrent Data Structures for NUMA Architectures - Calciu, Irina; Balakrishnan, Mahesh; Aguilera, Marcos; Sen, Siddhartha (Proc. 22nd ACM International Conference on Architectural Support for Programming Languages and Operating Systems (ASPLOS), 2017)
No Abstract Available.